Coordination Polymers of Some Lanthanide(III) Nitrate With Schiff Bases - Dwivedi, D.K.; Shukla, B.K.; Shukla, R.K. (Asian Journal of Chemistry, 2010)
The Schiff bases derived from 2-hydroxy-1-naphthaldehyde and salicylaldehyde with o-dianisidine, p-phenylene diamine and benzidine and their lanthanide(III) complexes have been synthesized and characterized by elemental, I.R. thermal, magnetic and D.R.S. studies.